2005
DOI: 10.1016/j.devcel.2005.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Echinoid Is a Component of Adherens Junctions That Cooperates with DE-Cadherin to Mediate Cell Adhesion

Abstract: Echinoid is an immunoglobulin domain-containing transmembrane protein that modulates cell-cell signaling by Notch and the EGF receptors. We show that, in the Drosophila wing disc epithelium, Echinoid is a component of adherens junctions that cooperates with DE-Cadherin in cell adhesion. Echinoid and beta-catenin (a DE-Cadherin interacting protein) each possess a C-terminal PDZ domain binding motif that binds to Bazooka/PAR-3; these motifs redundantly position Bazooka to adherens junctions. Echinoid also links … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
192
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 176 publications
(216 citation statements)
references
References 72 publications
11
192
2
Order By: Relevance
“…Asymmetric and complementary distributions of Myosin II and Baz have not been reported previously in the context of normal wing development, but have been described in association with clones of cells mutant for the transmembrane immunoglobulin domain encoding gene echinoid (Wei et al, 2005;Laplante and Nilson, 2006). Echinoid protein (Ed) localizes to the adherens junction in wing imaginal disc cells, can bind to Baz, and appears to act as a cell adhesion molecule (Wei et al, 2005).…”
Section: Accumulation Of Myosin II At the D-v Compartment Boundarymentioning
confidence: 87%
See 3 more Smart Citations
“…Asymmetric and complementary distributions of Myosin II and Baz have not been reported previously in the context of normal wing development, but have been described in association with clones of cells mutant for the transmembrane immunoglobulin domain encoding gene echinoid (Wei et al, 2005;Laplante and Nilson, 2006). Echinoid protein (Ed) localizes to the adherens junction in wing imaginal disc cells, can bind to Baz, and appears to act as a cell adhesion molecule (Wei et al, 2005).…”
Section: Accumulation Of Myosin II At the D-v Compartment Boundarymentioning
confidence: 87%
“…Recent studies have revealed that in certain contexts, Myosin II and Par-3 exhibit asymmetric and complementary distributions (Zallen and Wieschaus, 2004;Wei et al, 2005). Par-3 is encoded in Drosophila by the bazooka gene (baz).…”
Section: Accumulation Of Myosin II At the D-v Compartment Boundarymentioning
confidence: 99%
See 2 more Smart Citations
“…Our attempts to determine the contribution of Velis and S-SCAM in ␤-catenin-dependent regulation of synaptic AMPARs were inconclusive, and Par-3, whose binding to ␤-catenin has been recently reported (40), or additional as yet to be identified ␤-catenin-interacting PDZ proteins could provide a link to the AMPAR modification. Other non-PDZ interactions of ␤-catenin could also play a role.…”
Section: Discussionmentioning
confidence: 99%